2018
DOI: 10.1002/2475-8876.12024
|View full text |Cite
|
Sign up to set email alerts
|

Folded roof house—Design solution to optimize environmental conditions with generic equipment and techniques

Abstract: We covered a rectangular site in a residential area oriented at a 45° angle to the north and rotated the roof of the second floor on top of the rectangular first floor; then, we created a large window on the side at the south corner. To achieve an open interior with a limited footprint, we created a single‐volume space connecting the first floor to the second floor with stairs. The timber frame of the second floor sits on the concrete box of the first floor. The stiff timber box consists of a folded roof and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…1 In the research field of indoor environmental design, several research outcomes have been reported to create a healthy, comfortable and productive indoor environment. [2][3][4] Many researchers have suggested a comprehensive estimation method based on numerical analysis techniques, including computational fluid dynamics (CFD), because of its usefulness in estimating IEQ using coupled simulation with heat/mass transfer analysis. [5][6][7][8][9][10][11][12][13][14] The obtained quantitative/qualitative analysis results enabled detailed estimation of IAQ and thermal environment, which 1 have been commonly applied in the field of indoor environmental design.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the research field of indoor environmental design, several research outcomes have been reported to create a healthy, comfortable and productive indoor environment. [2][3][4] Many researchers have suggested a comprehensive estimation method based on numerical analysis techniques, including computational fluid dynamics (CFD), because of its usefulness in estimating IEQ using coupled simulation with heat/mass transfer analysis. [5][6][7][8][9][10][11][12][13][14] The obtained quantitative/qualitative analysis results enabled detailed estimation of IAQ and thermal environment, which 1 have been commonly applied in the field of indoor environmental design.…”
Section: Introductionmentioning
confidence: 99%
“…1 Improving IAQ without increasing energy costs is a crucial building design consideration for achieving sustainability. 2 Volatile organic compounds (VOCs) are well-known indoor air pollutants which deteriorate the IAQ directly and can also have adverse health effects, e.g. they can cause allergy and sick building syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Against this background, the Architectural Institute of Japan launched the Japan Architectural Review (JAR) in January 2018 as a unique peer‐reviewed international journal . The overarching purpose of launching JAR was (a) to republish high‐quality papers that were published in Transactions of AIJ in Japanese as translated papers in English for the international academic community, and (b) to provide a platform for publishing original research papers covering all fields of architecture, from design to engineering …”
mentioning
confidence: 99%